FAUNA IKAN DARI SUNGAI TENAYAN, ANAK SUNGAI SIAK, DAN RAWA DI SEKITARNYA, RIAU - Chaidir P Pulungan (Berkala Perikanan Terubuk, 2009)
A research on fishes in the Tenayan river and in the swamp aroundthe river has been conducted on July to October 2008 and January to February2009. Fish samples were taken at three sites namely in the downstream, upstreamand in the swamp around downstream area. The fishes collected by gill-net, fishtrap and scoop-net. The specimen was identified based on weber and De Beaufort(1913 and 1916), Nelson (1976), Saanin (1986) dan Kottelat et al. (1993). Fishescollected are belonged to order Cypriniformes (14 species), Siluriformes (4species), Cyprinodontiformes (14 species) and Perciformes (10 species). Mostspecimen from the upper stream belonged to order Cypriniformes andCyprinodontiformes, while fishes capture in the swamp around the downstreamarea mainly belonged to order Perciformes. Surprisingly, a new species that hasnot been collected in the zoological museum, LIPI, Cibinong was capture in thestudy area and this fish is identified as Esomus sp. Fishes that are present in thestream mostly categorized as the primary family. Fish species that are abundancein the stream are Esomus sp.